Fort Jesus: guiding the past and contesting the present in Kenya - Sarmento, João (2019)
This paper focuses on the interpretation of Fort Jesus, Kenya, a late sixteenth century Portuguese-built fort, and attempts to discuss its significance in the region and in the country, and its role within the context of recent tourism development in Kenya. By exploring the ways in which a sample of local tourist guides engage with tourists and with the heritage and memory that Fort Jesus represents in this coastal region, some of the challenges facing tourism development in post-colonial Kenya are analysed. While the study reveals that the guides are not a homogeneous group, one of the shared positions is their resentfulness towards the inability of the coastal region to control and benefit from tourism. At the same time, despite some of the guides revealing to be skilful cultural mediators, the vast majority construct their mediation upon a predominantly colonial knowledge of the Fort.